Role of transmembrane pH gradient and membrane binding in nisin pore formation. - Moll, G N (1997)
Nisin is a cationic antimicrobial peptide that belongs to the group of lantibiotics. It is thought to form oligomeric pores in the target membrane by a mechanism that requires the transmembrane electrical potential delta psi and that involves local pertubation of the lipid bilayer structure. Here we show that nisin does not form exclusively voltage-dependent pores: even in the absence of a delta psi, nisin is able to dissipate the transmembrane pH gradient (delta pH) in sensitive Lactococcus lactis cells and proteoliposomes. The rate of dissipation increases with the magnitude of the delta pH. Nisin forms pores only when the delta pH is inside alkaline. The efficiency of delta psi-induced pore formation is strongly affected by the external pH, whereas delta pH-induced pore formation is rather insensitive to the external pH. Nisin(1-12), an amino-terminal fragment of nisin, and (des-deltaAla5)-(nisin(1-32) amide have a strongly reduced capacity to dissipate the delta psi and delta pH in cytochrome c oxidase proteoliposomes and L. lactis cells. Both variants bind with reduced efficiency to liposomes containing negatively charged phospholipids, suggesting that both ring A and rings C to E play a role in membrane binding. Nisin(1-12) competes with nisin for membrane binding and antagonizes pore formation. These findings are consistent with the wedge model of nisin-induced pore formation.